Які книжки привіз Іван Франко з Києва 1909 р.? - Бурлака, Г. (Слово і Час, 2022)
У статті розглянуто один із епізодів формування бібліотеки Івана Франка, який усе життя активно цікавився книжками. Його колекція була
рухливим організмом: він стежив за новинками, замовляв звідусіль видання за каталогами, щедро ділився своїми книжками. Окрема, ще не до кінця
вивчена тема — дарчі написи на примірниках бібліотеки І. Франка. Немало видань цього зібрання мають печатки чи наклейки книгарів різних
міст і країн, зокрема й тих, де І. Франко ніколи не бував. В архіві збереглися книжкові реклами й каталоги, листування з видавцями й букіністами. На основі проведених спостережень констатовано, що «прив’язувати»
комплектацію бібліотеки І. Франка до його поїздок — не надто продуктивна справа. The paper focuses on the episode of the formation of Ivan Franko’s library. Franko was actively
interested in books all his life, and his collection was a mobile organism: he followed
the new editions, ordered catalogs from everywhere, and generously shared his books. The
unique library has survived to this day as part of the writer’s archival collection. Both modern
editions and old prints (which are rather numerous) retain evidence of their movements.
Gift inscriptions, bookplates, stamps of institutions and organizations, notes and marks on
the margins — all these pieces of evidence complement the information about Franko’s
circle of communication and creative interests, being an important source for studying his
biography. It is impossible to completely reconstruct the history of acquiring the books that
form this memorial collection, but a number of facts give grounds for some conclusions on
this issue. Franko’s unexpected visit to Kyiv in 1909 is described in many memoirs, but only
D. Doroshenko, who accompanied the writer to the bookstores, briefly told what publications
his companion was interested in, and which booksellers he met, naming several particular places they visited. The traces of these locations in the books from the collection may
serve as proof that the writer brought them from his trip. Now working with Franko’s personal
library, the author of the paper is trying to fi nd out which books from Kyiv enriched
Franko’s collection. The testimonies by D. Doroshenko, bookplates, ownership inscriptions
and stamps, numbers of books assigned by the owner of the library, and other data were
taken into account. Many editions of this collection have stamps or stickers of booksellers
from different cities and countries, including those that Franko never visited. The writer’s
archive also contains book advertisements and catalogs, as well as his correspondence
with publishers and second-hand booksellers. Th us, generally linking the collection of Ivan
Franko’s library to his travels proves to be not a very productive task.